Capital and Crisis: A Metafictional Study of Wealth and Power in Hernan Diaz’s Trust - Ghimire, Sushil (Voice of Teacher, 2023)
This paper examines how Hernan Diaz’s novel Trust (2022) uses metafictional techniques to explore the relationship between wealth and power in the context of the Great Depression. The paper argues that Diaz’s novel challenges the dominant narratives of capitalism and exposes the hidden mechanisms of exploitation and oppression that sustain the system. The paper analyzes the four sections of the novel, which consist of a novel, an autobiography, a memoir, and a private diary, each with its own author, audience, and agenda. The paper shows how these texts interact and contradict each other, creating a complex and multifaceted representation of the wealthy Rask family and their impact on society. The paper concludes that Diaz’s novel is a powerful critique of the capitalist system and its effects on human lives, as well as a reflection on the role of fiction and storytelling in shaping our understanding of reality.